Academic mobility in the Anthropocene era: a comparative study of university policy at three New Zealand institutions. Issue 3 (3rd March 2016) - Hopkins, Debbie; Higham, James; Tapp, Sarah; Duncan, Tara
Abstract : Anthropogenic climate change is a wicked problem, requiring fundamental behavioural and technological responses now, in the Anthropocene, a term denoting the current era of human dominance of biological, chemical and geological processes on Earth. Travel and transport policies are key to effective responses, confronting both leisure and business travellers, including academics. This paper explores in detail the factors that promote or suppress academic travel, examining institutional policies which frame academic mobility practices at three New Zealand universities; University of Otago, University of Auckland and Victoria University of Wellington. It finds evidence of little congruence between sustainability statements, with their wide discourses on environmental sustainability, and the institutional policies governing academic mobility. Three overriding themes emerging from the analysis are presented: hollow words (describing a lack of meaningful commitment to sustainability, with disconnections between sustainability rhetoric and key policies), unspoken words (assumptions about the necessity of travel) and facilitating mobilities (promoting travel, rewarding those who travel). These themes highlight varying degrees of divergence between the sustainability imperatives of these universities and the carbon emissions of institutionalised academic mobilities. Concluding remarks highlight opportunities for New Zealand's academic institutions to align travel policies with growing sustainability imperatives and discuss future research directions.